User Location and Tracking in an In-Building Radio Network - Bahl, Paramvir; Padmanabhan, Venkata N.; Padmanabhan, Venkat; Bahl, Victor (1999)
The proliferation of mobile computing devices and local-area wireless networks has fostered a growing interest in location-aware systems and services. A key requirement for enabling such services is user location and tracking. In this paper we address this problem in the context of a popular radio-frequency wireless network technology. Our approach is based on recording and processing real-time signal strength information available at multiple base stations positioned to provide overlapping coverage in the area of interest. We employ techniques that combine empirical measurements with signal propagation modeling. We present concrete experimental results that demonstrate the feasibility of estimating user location with a high degree of accuracy.